Expression of red/green-cone opsin mutants K82E, P187S, M273K result in unique pathobiological perturbations to cone structure and function - Sechrest, Emily R.; Barbera, Robert J.; Ma, Xiaojie; Dyka, Frank; Ahn, Junyeop; Brothers, Brooke A.; Cahill, Marion E.; Hall, Isaac; Baehr, Wolfgang; Deng, Wen-Tao (Frontiers in Neuroscience, 2024)
Long-and middle-wavelength cone photoreceptors, which are responsible for our visual acuity and color vision, comprise ~95% of our total cone population and are concentrated in the fovea of our retina.Previously, we characterized the disease mechanisms of the L/M-cone opsin missense mutations N94K, W177R, P307L, R330Q and G338E, all of which are associated with congenital blue cone monochromacy (BCM) or color-vision deficiency. Here, we used a similar viral vector-based gene delivery approach in Mopsin knockout mice to investigate the pathogenic consequences of the BCM or color-vision deficient associated L-cone opsin (OPN1LW) mutants K82E, P187S, and M273K. We investigated their subcellular localization, the pathogenic effects on cone structure, function, and cone viability. K82E mutants were detected predominately in cone outer segments, and its expression partially restored expression and correct localization of cone PDE6α' and cone transducin γ. As a result, K82E also demonstrated the ability to mediate cone light responses. In contrast, expression of P187S was minimally detected by either western blot or by immunohistochemistry, probably due to efficient degradation of the mutant protein. M273K cone opsin appeared to be misfolded as it was primarily localized to the cone inner segment and endoplasmic reticulum. Additionally, M273K did not restore the expression of cone PDE6α' and cone transducin γ in dorsal cone OS, presumably by its inability to bind 11-cis retinal. Consistent with the observed expression pattern, P187S and M273K cone opsin mutants were unable to mediate light responses. Moreover, expression of K82E, P187S, and M273K mutants reduced cone viability. Due to the distinct expression patterns and phenotypic differences of these mutants observed in-vivo, we suggest that the pathobiological mechanisms of these mutants are distinct.